2017
DOI: 10.1002/joc.5333
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate trends and topographic influence over the Western Ghat catchments of India

Abstract: This study investigates the role of elevation stratification and climate change on the hydrology of Western Ghat catchments during the period from 1951 to 2013 using gridded data. The trend analysis of rainfall and temperature was conducted using the Mann–Kendall trend test, and the hydrological modelling of the rivers was conducted using the Soil and Water Assessment Tool (SWAT) model. To characterize the spatial distribution of rainfall and streamflow based on elevation stratification, contemporary rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 68 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…It could be observed that the maximum annual average rainfall does not occur at the high altitude of the Western Ghats, which may be due to the nonlinear temperature dependence of the saturation pressure. Similar findings were observed by [33], which indicated that the peak rainfall in the Western Ghats is 50 km away on the windward side from the crest. From the time series plot of daily rainfall (Figure 3), it can be observed that CHIRPS-0.25 and CHIRPS-0.05 precipitation products detect a higher amount of rainfall during the monsoon season when compared with TRMM precipitation data.…”
Section: Categorical and Continuous Statistical Metricssupporting
confidence: 85%
See 3 more Smart Citations
“…It could be observed that the maximum annual average rainfall does not occur at the high altitude of the Western Ghats, which may be due to the nonlinear temperature dependence of the saturation pressure. Similar findings were observed by [33], which indicated that the peak rainfall in the Western Ghats is 50 km away on the windward side from the crest. From the time series plot of daily rainfall (Figure 3), it can be observed that CHIRPS-0.25 and CHIRPS-0.05 precipitation products detect a higher amount of rainfall during the monsoon season when compared with TRMM precipitation data.…”
Section: Categorical and Continuous Statistical Metricssupporting
confidence: 85%
“…IMD, TRMM, and CHIRPS-0.25 were utilised to run the model for comparison. were observed by [33], which indicated that the peak rainfall in the Western Ghats is 50 km away on the windward side from the crest. From the time series plot of daily rainfall (Figure 3), it can be observed that CHIRPS-0.25 and CHIRPS-0.05 precipitation products detect a higher amount of rainfall during the monsoon season when compared with TRMM precipitation data.…”
Section: Hydrological Signaturesmentioning
confidence: 97%
See 2 more Smart Citations
“…Geologically, the basin is of Precambrian formations. The upper part of the basin mainly consists of sandy clay loam soil, while the lower parts consist of clay loam soil 38 . Mountainous dense forests cover the upstream parts of the basin while agricultural and urban lands dominate the lower parts.…”
Section: Study Areamentioning
confidence: 99%